Pengaruh Media Evaluasi Pembelajaran Baamboozle terhadap Kemampuan Mengulas Karya Fiksi (Novel) Siswa Kelas VIII SMP Negeri 5 Parepare - Rosmawati, Rosmawati; Nurhusna, Nurhusna; Wijayanti, Tuti (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to determine the effect of the Baamboozle learning evaluation media on students’ ability to review fictional works (novels) within the context of Indonesian language learning. The research employed a quantitative approach with a pre-experimental design (one-group pretest–posttest). The data were analyzed using descriptive and inferential statistical tests at a 0.05 significance level. The parametric analysis (paired sample t-test) produced a significance value of 0.001 (< 0.05) with a tvalue of -19.110, indicating that H₀ was rejected and H₁ was accepted. These results confirm that the use of Baamboozle has a significant effect on the reviewing skills of eighth-grade students at SMP Negeri 5 Parepare. Improvements were evident in students’ ability to understand the definitions and types of fictional works, identify intrinsic elements of novels, classify linguistic features, and compose coherent and well-structured reviews.